First Principles Study of the Electronic and Magnetic Properties of PrVSb3 and PrSrVSb3 - Bhandari, Shalika R.; Kaphle, Gopi C.; Ghimire, Madhav P. (Bhairahawa Campus Journal, 2021)
Abstract available with the full text.